Wings Over Illinois - Abney, Gene (Book collections on Project MUSE., 2007)
Wings over Illinois recounts World War II veteran Arthur Abney's illustrious aviation career, effectively documenting a span in our own nation's history from the vantage of the skies. Abney describes a lifetime of experience, from his time as an eager young pilot with the Flying Egyptians to his tour of service during World War II, his years with the Illinois Department of Aeronautics, American Airlines, and the Southern Illinois University Aviation Management and Flight program. Abney introduces readers to hangar flying-exciting end-of-day flig.